Effect of thermal and thermo-mechanical processing on Mg-Sn-Zn alloy and understanding structure-property correlation. (2020) - Vignesh, P.; Venkatesh, G.; Kumaran, S.
Abstract: In this study, Mg-5Sn-5Zn alloy was fabricated and conditioned by thermal and thermo-mechanical treatment. The microstructure and phase evolution of the processed alloy were investigated by Optical microscope and X-ray diffraction studies. The tensile test results show that hot extruded alloy shows higher strength with limited ductility than the as-cast and homogenized Mg-5Zn-5Sn alloy. While homogenized alloy shows better ductility 4fold better than the extruded and 2fold than as-cast alloy. Electrochemical polarization test was conducted in a NaCl solution. The corrosion rate depends on Mg2 Sn and MgZn2 to achieve high corrosion resistance, the tin and zinc should dissolve in Mg- matrix that is the homogenized sample at 400 °C for 13hrs has the lower corrosion rate.